2012
DOI: 10.1002/ijc.27569
|View full text |Cite
|
Sign up to set email alerts
|

Taurolidine: Mode of administration in mouse tumor models

Abstract: Our study protocols with taurolidine for the treatment of osteosarcoma (OS) in two syngeneic OS mouse models with K7M2 cells intravenously (i.v.) injected into BALB/c mice and with LM8 cells subcutaneously (s.c.) inoculated in C3H mice 1 were based on intraperitoneal (i.p.) treatment regimens that were previously reported to be successful in three different mouse tumor models. [2][3][4] Braumann in his letter to the editor criticized that we did not determine the maximal tolerated dose (MTD) in our study and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…However, one recent publication reported that long-term high-dose treatment with taurolidine caused severe hepatic injury in a murine osteosarcoma model [ 30 ]. Therefore, the authors suggested caution before widespread use of taurolidine as an anti-cancer drug in clinical oncology [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, one recent publication reported that long-term high-dose treatment with taurolidine caused severe hepatic injury in a murine osteosarcoma model [ 30 ]. Therefore, the authors suggested caution before widespread use of taurolidine as an anti-cancer drug in clinical oncology [ 31 ].…”
Section: Introductionmentioning
confidence: 99%